Hypomnemata for a Contradiction to Inhabit - Sánchez-Mateos Paniagua, Rafael (Re-visiones, 2024)
In this hypomnémata we share a set of readings and notes, trying to briefly focus on a series of events in time but nonactual in many senses, that concern the fields of culture, art, and its relationship to politics, most of which have taken place in the city of Madrid. Due to their fragility (or their exposure to oblivion) we want make them available as supports –in Foucault’s terms– for a future review, reflection and meditation, either collectively or individually, because it involves a set of not yet assumed contradictions. An act of personal memoir that, in the round trip journey from writing to reading, might concern many more people. Its availability –as Foucault points out on hypomnémata writing– opens possibilities of subjectification between the self and the world , –therefore this form is proposed to the calling of the present issue. We are wondering how the image and the gaze, or the forms and their perception, are related in this writing of the self, which we believe will only reach political meaning when put in relation to others.